2019 IEEE/CVF International Conference on Computer Vision Workshop (ICCVW) 2019
DOI: 10.1109/iccvw.2019.00178
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Shot Hyperspectral Image Denoising With Separable Image Prior

Abstract: Supervised learning with a convolutional neural network is recognized as a powerful means of image restoration. However, most such methods have been designed for application to grayscale and/or color images; therefore, they have limited success when applied to hyperspectral image restoration. This is partially owing to large datasets being difficult to collect, and also the heavy computational load associated with the restoration of an image with many spectral bands. To address this difficulty, we propose a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…DSConv can extract local delicate features of the image by considering the information of the position and channel separately. Imamura et al designed a denoising network for hyperspectral images using DSConv and demonstrated its ability to realize efficient restoration [ 46 ]. The advantage of DSConv is that it reduces the number of network parameters and the computational complexity in convolution operations [ 42 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…DSConv can extract local delicate features of the image by considering the information of the position and channel separately. Imamura et al designed a denoising network for hyperspectral images using DSConv and demonstrated its ability to realize efficient restoration [ 46 ]. The advantage of DSConv is that it reduces the number of network parameters and the computational complexity in convolution operations [ 42 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…In recent works, it is observed that learning-based techniques are utilized for noise reduction in HSI data. Some notable contributions include [25], [26], [27], [28], [29] and [30]. Authors in [25] employ a cubic noisy-clean image learning approach where non-linearity functions are also trainable along with convolutional weights and biases.…”
Section: Related Workmentioning
confidence: 99%
“…Inspired by the pioneering work of Deep Image Prior (DIP); noisy HSI data is recovered in [27] using the assumption of prior introduced by untrained neural network and early stopping as the regularization strategy. A self-supervised learning approach using separable image prior is explored in [26]. However, since most of these models [25]- [29] are not trained over mixed noise in corrupted HSI data; they yields sub-optimal results when these techniques are tested over real HSI data.…”
Section: Related Workmentioning
confidence: 99%
“…Self-supervised techniques also rely on the observed image for training while they create their own training sets from the observed noisy image to train the deep network. In [90], a self-supervised (Zero-shot) denoising technique was proposed for HSIs in which CNN was trained based on the observed image, which is assumed to be the target, and an input image, which is obtained by adding noise to the observed image. Therefore, the network can be only trained using the observed image.…”
Section: B Deep Learning-based Techniquesmentioning
confidence: 99%